AKTIVITAS CMC-ase KHAMIR Candida sp. YANG DIISOLASI DARI TANAH KEBUN BIOLOGI WAMENA, PAPUA - Atit Kanti; I Made Sudiana (BERITA BIOLOGI, 2003)
Cellulolytic Candida sp.was isolated from Wamena, Papua.The strain was able to grow in media with carboxymethyl cellulose as a sole carbon source implying that the isolate produced 1-3 oc endo-gluconase.To study the effect of glucose and osmotic pressure on 0.1% glucose and 0.1% NaCl were augmented to CMC-contained media.Glucose augmentation affects cellulolytic activity of culture,probably due to higher biomass production in media. NaCl addition appear not to affect cellulolytic ability. Profile of pH also varied depend on the cultivation media. Maximum growth rate was achieved when glucose was added which was implying that glucose stimulate cell growth.